What happens after the catchment caught the storm? Hydrological processes at the small, semi-arid Weatherley catchment, South-Africa - (:unkn) unknown (My University, 2005)
The knowledge of water flow pathways and residence times in a catchment are essential for predicting the hydrological response to a rain storm event. Different experimental techniques are available to study these processes, which are briefly reviewed in this paper. To illustrate this, recent findings from the Weatherley catchment a 1.5 km2 semi-arid headwater in South-Africa, are reported in this paper. Beside classical hydrometric measurements of precipitation and runoff different experimental techniques were applied to explore flow paths (i.e. soil moisture and groundwater measurements, natural tracers, and 2-D electrical resistivity tomographies (ERT)).
Keywords: African Research